The Effectiveness of Educational Game-Based Learning Media in Increasing Student Learning Motivation - Annora Theda Mufarrihah; Mochamad Ridwan (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2026)
Student motivation in Physical Education can be enhanced by using innovative educational game-based learning media through Educaplay. Thus, this study assesses how well educational game-based learning media boost students' media to learn. A quantitative pre-experimental study with a one-group pretest-posttest design was the methodology. The population was 320, and the sample size was 32 students, using random sampling. This study showed a significant difference between the pretest and posttest after hypothesis testing using a paired sample t-test. Since the significance value is 0.000<0.05, Ha is accepted and H0 is refused. With an N-gain score of 0.690 and an N-gain percentage of 69.00, Educaplay's effectiveness level in boosting motivation is classified as quite effective after the N-gain test. Therefore, Educaplay's educational game-based learning materials are quite successful in boosting students' motivation for Physical Education learning.